Workshop Pembuatan E-Modul berbasis Canva - Haryanti Putri Rizal; Sitti Sapiah; Meili Yanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Teachers are currently required to be able to develop students' skills to face the challenges of the 21st century. Teaching materials are one of the important learning support elements that need to be continuously developed, in the form of books, modules, videos and infographics. Community service with the title workshop on making Canva-based E-Modules at SDN 49 Pasanggarahan, Majene district was appointed as an effort to increase teacher competence in making E-Modules that are more interesting and interactive than if they were made in Ms Word. In the process of making it, teachers are also expected to be more adept at sorting essential material and according to the cognitive stages of elementary school students. The method used is the training method, namely providing material presentation accompanied by training for teachers regarding creating E-Modules using the Canva application. The results of this activity showed that overall the activity was in line with participants' expectations (71%) and participants strongly agreed that the workshop held could improve participants' abilities regarding creating Canva-based e-modules (79%).